A novel block copolymer with excellent amphiphobicity synthesized via ARGET ATRP. Issue 13 (10th March 2016) - Qian, Tao; Wang, Juanjuan; Cheng, Tiantian; Zhan, Xiaoli; Zhang, Qinghua; Chen, Fengqiu
ABSTRACT: The poly(methyl methacrylate) ‐b‐ poly(2‐[[[[2‐(perfluorohexyl)]‐sulfonyl]‐amino]ehthyl] methacrylate) (PMMA ‐b‐ PC6 SMA) copolymers were successfully synthesized for the first time using activator regenerated by electron transfer atom transfer radical polymerization (ARGET ATRP) method. Under optimized reaction conditions, the degree of polymerization (DP) of resulting copolymers increased approximately linearly with monomer conversion. Structures of a well‐defined block copolymer were determined by GPC, FT–IR, and 1 H‐NMR spectra. Results from AFM and contact angle measurements of polymer films revealed the presence of block segments derived from PC6 SMA, as indicated by the obvious increase in hydrophobicity and oleophobicity. The relationship between surface composition and surface wetting ability was confirmed by XPS and AFM spectra. Compared with the random copolymer PMMA ‐co‐ PC6 SMA, C6 SMA dosages in the PMMA ‐b‐ PC6 SMA copolymers were greatly decreased, which retained its hydrophobic and oleophobic properties. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 2040–2049 Abstract : Compared with the random copolymer, the fluorinated block copolymer with low content of short perfluoroalkyl acrylate synthesized by ARGET ATRP displays obvious phase separation on the coated films and performs excellent water and oil repellence. PMMA103 ‐ b ‐PC6 SMA12.3 ‐treated fabrics and polyurethane foam, which has multi‐scale structure, can resist most kinds of liquids. Thus, the block copolymer PMMA‐ b ‐C6 SMA provides a value joint between block copolymer structure and surface wettability, which has a potential in the practical application.